The Poisoning Effect of Al and Be on Mg—1 wt.% Zr Alloy and the Role of Ultrasonic Treatment on Grain Refinement - Balasubramani, Nagasivamuni; Wang, Gui; StJohn, David H.; Dargusch, Matthew S. (Frontiers in Materials, 2019)
AAddition of Al – Be master alloy to a Mg – Zr alloy reduces melt oxidation, however, it has a detrimental grain coarsening effect that is believed to be caused by an unknown interaction of Be with the Zr nucleant particles. However, this study found that Al is the major cause of grain coarsening. By analysis of intermetallic phases and chemical analysis for solute Zr, it was revealed that Al reacts with the undissolved α – Zr particles forming Zr – Al intermetallic phases and reducing the amount of solute Zr both of which lead to a decrease in the grain refinement efficiency of the master alloy. Despite this negative effect of Al on grain refinement, application of ultrasonic treatment produces significant grain refinement of the Mg – Zr – Al – Be alloy demonstrating the potential for developing ignition-proof and grain refined Mg alloys.